Assessing the Representation of Ethnic and Madeshi Communities in Nepal's Federal and Provincial Parliament: A Study of 2022 Election - Adhikari, Rishiram (International Research Journal of MMC, 2023)
Without political representation it is impossible to participate in policy formulation procedure so that political representation is important for inclusion. Nepal also follows the inclusive democratic political system and constitutionally guaranteed political representation of women, minorities, Dalit and indigenous nationalities through adopting mixed (direct and propositional) method of election system. In this context, the study concentrates on the political representation of Indigenous nationalities and Madeshi in 2022 general election, mainly in the house of representation in federal and province assembly. The main objective of the study is to analyze the situation of political representation of indigenous Dalit, and Madeshi people as well as women in both federal and province assembly province parliament. Qualitative method was used to analyze the data and information collected from secondary sources. Conclusion and findings of this study are based on data presentation and analysis. Constitutional provision which could not properly work in the direction of inclusive representation in Nepal is the main finding of this study.